Survey of wild fauna in rehabilitation centre of environment military police battalion of 2010, 2011 and 2013 in the municipality of Candeias Jamari-RO - Lima, Renato Abreu; Silva, Sumara Matos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Our planet is inhabited by many millions of species, and it is worth to mankind in ecological aspects, scientific, economic and cultural. In Brazil we have the greatest diversity of the planet that rises to the rank of major nation among 17 countries with the greatest biodiversity. The Environmental Military Police Battalion (BPA) mission is to plan, coordinate and implement policing, aiming to protect animals and the environment. And it is at the Center for Rehabilitation of Wild Animals (CRAS) that animals seized or collected are given to assess your physical condition, treat these animals and then release them into the environment. The study aimed to survey the wildlife species collected in CRAS/BPA, from 2010, 2011 and 2013. We analyzed records obtained from reports prepared by CRAS, and it was established that 185 species of birds were the most prevalent species, as presented, approximately 52.43% of the total, followed by mammals, with approximately 29.18%, and finally, reptiles, with 18.37%.